Microbial evolution - Ochman, Howard,Ed (Cold Spring Laboratory Press, 2016)
"Bacteria have been the dominant forms of life on Earth for the past 3.5 billion years. They rapidly evolve, constantly changing their genentic architecture through horizontal DNA transfer and other mechanisms. Consequently, it can be difficult to define individual species and determine how they are related. Written and edited by experts in the field, this collection from Cold Spring Harbor Perspectives in Biology examines how bacteria and other microbes evolve, focusing on insights from genomics-based studies. Contributors discuss the origins of new microbial populations, the evolutionary and ecological mechanisms that keep species separate once they have diverged, and the challenges of construction phylogenetic trees that accurately reflect their relationships. They describe the organization of microbial genomes, the various mutations that occur, including the birth of new genes de novo and by duplication, and how natural selection acts on those changes. The role of horizontal gene transfer as a strong driver of microbial evolution is emphasized throughout. The authors also explore the geologic evidence for early microbial evoluiton and describe the use of microbial evolution experiments to examine phenomena like natureal selection. This volume will thus be essential reading for all microbial ecologists, population geneticists, and evolutionary biologists